On the First Curve in the FučiK Spectrum with Weights for a Mixed p-Laplacian - LEADI, LIAMIDI ARÈMOU; MARCOS, ABOUBACAR (My University, 2007)
We show the existence of a first curve in the Fučik spectrum with weights for the p- Laplacian under mixed boundary conditions. We also study the asymptotic behavior of this first curve.
Keywords: p-Laplacian operator; principal eigenvalue; Fucik spectrum